The Shuberts present : 100 years of American theater (Harry N. Abrams, 2001)
A tribute to the brothers Shubert and their entertainment dynasty, with sections on each of their Broadway theaters, including hundreds of detailed historical and contemporary architectural photographs, production stills, gatefolds, memorabilia, and more.